Parenting influences on bullying and victimization - Baldry, Anna Costanza (Legal and criminological psychology, 1998)
Purpose. The main aim of this research was to investigate the parental styles and personal characteristics of bullies and victims, and to disentangle factors related to bully/victims from factors related to children who were only bullies or only victims. Method. A self-report questionnaire on bullying was completed by 113 girls and 125 boys aged 11-14 years in a middle school in Rome. Results. Over half of all students had bullied others in the previous three months, and nearly half had been victimized. About a quarter of all students were both bullies and victims. Bullies tended to be male and to have low pro-social behaviour, but these were largely characteristics of children who were only bullies. Victims tended to be female and to have low self-esteem, but these were largely characteristics of children who were only victims. Children who were both bullies and victims tended to have authoritarian parents, but these were largely characteristics of bully/victims. Conclusions. It is important to study only bullies, only victims and bully/victims, as well as bullies and victims in general. Personal characteristics were related to only bullies or only victims, whereas parental styles were more related to bully/victims.